Hall of Mirrors: Corporate Philanthropy and Strategic Advocacy. Issue 4 (2nd July 2021) - Bertrand, Marianne; Bombardini, Matilde; Fisman, Raymond; Hackinen, Brad; Trebbi, Francesco
Abstract: Information is central to designing effective policy, and policy makers often rely on competing interests to separate useful from biased information. We show how this logic of virtuous competition can break down, using a new and comprehensive data set on U.S. federal regulatory rulemaking for 2003–2016. For-profit corporations and nonprofit entities are active in the rulemaking process and are arguably expected to provide independent viewpoints. Policy makers, however, may not be fully aware of the financial ties between some firms and nonprofits—grants that are legal and tax-exempt but hard to trace. We document three patterns that suggest that these grants may distort policy. First, we show that shortly after a firm donates to a nonprofit, the nonprofit is more likely to comment on rules on which the firm has also commented. Second, when a firm comments on a rule, the comments by nonprofits that recently received grants from the firm's foundation are systematically closer in content to the firm's own comments, relative to comments submitted by other nonprofits. Third, the final rule's discussion by a regulator is more similar to the firm's comments on that rule when the firm's recent grantees also commented on it.